Evaluasi Usability Sistem Pelaporan Publikasi Penelitian Dosen Berbasis Android - Fransiskus Panca Juniawan; Laurentinus; Dwi Yuny Sylfania (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The research publication reporting system of the STMIK Atma Luhur lecturer is an android-based system used by the STMIK Atma Luhur lecturer to report their research publications to the LPPM Research Section. To find out whether the system used is running well, an evaluation is carried out. The evaluation focuses on the value of Usability which consists of five categories as independent variables, namely Efficiency (X1); Learnability (X2); Satisfaction (X3); Errors (X4); and Memorability (X5). In addition, the dependent variable is Overall Impression Usability (Y). We used 37 lecturers as respondents. The test method used is a validation test consisting of a correlation test and a reliability test; simple linear regression analysis test, and the comparison of the Significance value with the Alpha value used is 0.05. The tests conducted using SPSS version 25. From the validity test conducted, taken from the value of Pearson Correlation and Corrected Item - Total Correlation values ​​that have values ​​above 0.05 and the results are that all variables have values ​​above 0.05. From the reliability testing, all questions proved to be reliable from one to another according to Cronbach’s Alpha values ​​above 0.60. From the simple linear regression test, the results show that the Efficiency (X1), Learnability (X2), Satisfaction (X3), and Memorability (X5) variables have a significant effect on Overall Impression (Y). In addition, the Errors (X4) variable does not have a significant effect on the Overall Impressions (Y) variable.